The imprint of the geological inheritage and present dynamics on uruguayan inner shelf sediments (south-western Atlantic) - Burone, Leticia (2019)
The Uruguayan continental shelf is characterised by a unique hydrographic system, composed of the Río de la Plata buoyant plume (RdlP-BP), and by water masses of contrasting thermohaline characteristics. Below the RdlP-BP the southward-flowing Subtropical Shelf Water and the northward-flowing Subantarctic Shelf Water converge at the Subtropical Shelf Front, which is the shelf extension of the Brazil-Malvinas Confluence. Three main sedimentary environments can be described associated with; I) “Atlantic coastal sands” (i.e. onshore from the palaeovalley); II) the SW-NE running “RdlP palaeovalley” and; III) “Relict sands” (i.e., offshore of the RdlP palaeovalley). Three exposed sedimentary units (U1 to U3) identified from acoustic profiles and sediment cores (sedimentary characteristics of stratigraphic units) almost entirely restricted to the palaeovalley. The transect here studied intersects these three environments contributing thus with the description of the morphological setting and sedimentary coverture. Physical and geochemical data were integrated and used to characterise the sedimentary facies previously described in the inner shelf and to understand environmental control on the development of these facies. Sediments from U1 show the terrestrial imprint of the RdlP and drier regional conditions, while sediments that characterised U3 indicate a sandy facies (quartz and bioclasts: whole and fragmented shells and polychaetes tubes) corresponding to an ancient coast. This last (with approximately 11 m height), is probably related to sea-level stabilization, between 20 and 25 m occurring during the Upper Pleistocene and Holocene for the South-Western Atlantic. The sediment from U3 reflects the colder and drier conditions prevailing in the region during the formation of this facies (13.7 and 9.7 cal ka BP). Eroded sediments (e.g., from U3; ancient coast) are deposited inside the palaeovalley and on the onshore region (between the palaeovalley and coastal sands). Also, U1 extends from the palaeovalley covering the onshore region. The outcrop of warmer oceanic shelf waters was probably a consequence of the geomorphology of the palaeovalley (edge of the palaeovalley) and related to the still fall presence of waters typical of the austral warm season when higher advection of Brazil Current occurs over the shelf. In this regard, the mound-like feature should induce bottom water to rise, operating as a ramp. Productivity proxies (Si/Ti, Ba/Ti, Ca/Ti and P/Ti) present the highest values in these stations (S16-S18), reflecting the imprint of the upwelling in the sediment. The information reported in this work is particularly important to better understand sedimentological dynamics in the Uruguayan inner shelf and the Southwestern Atlantic region. It is also important for elaborating more precise paleoenvironmental and palaeoceanographic reconstructions.